Useful spontaneous hygroelectricity from ambient air by ionic wood. (1st June 2022) - Li, Yang; Cui, Jiedong; Shen, Haoyu; Liu, Chaocheng; Wu, Peilin; Qian, Zhiyun; Duan, Yulong; Liu, Detao
Abstract: Spontaneous electricity generator using moisture in ambient air has been developed rapidly in recent years for its great potential in self-sustained systems. However, due to the lack of efficient and continuous ion transport, the power-generation ability and stability from existing materials are unsatisfactory (ultra-low current, intermittent voltage and strong dependence on moisture) for practical applications. Here we report a generator made of ionic wood processed from natural wood using a simple and effective strategy to form continuous nanostructures with LiCl salts like spider webs around the inner walls of wood microchannels (i.e., fiber lumina). A single generator spontaneously produced a sustainable voltage of around 750 mV with a useful current of around 712 μA in ambient environment. And it also exhibited outstanding stability even when ambient humidity suddenly decreased to below 10% and stayed for 10 h. Besides, a connected system consisting of only six components outputted a voltage up to 4.40 V and current up to 4.16 mA, which can power LED lights. Our ionic wood shows promise for ambient moisture-energy conversion to develop the next self-sustained power system, with low-cost, sustainability and easily larger-scale productions. Graphical Abstract: We investigate herein a hydroelectric device made of ionic wood that can spontaneously produce a useful stable electricity (e.g. 712 μA current) from ambient humidity. The ionic wood processed directly from natural wood by a simple effective strategy to form unique nanostructures like spiderwebs on the inner walls of microchannels. The generator exhibited exceptional stability even under harsh ambient humidity compared to the exiting materials. ga1 Highlights: High strength aerogel wood was made directly from natural wood by a simple strategy. Ionic wood has unique ionic nanostructure like spiderwebs on inner walls of channels. A generator made of ionic wood outputs a useful power with charge-discharge behaviors. Electrical output shows exceptional stability even in an extreme humidity environment.